Occupational health hazards in the interventional laboratory: progress report of the Multispecialty Occupational Health Group. (26th August 2010) - Miller, Donald L; Klein, Lloyd W; Balter, Stephen; Norbash, Alexander; Haines, David; Fairobent, Lynne; Goldstein, James A; ,
Abstract : The Multispecialty Occupational Health Group (MSOHG), formed in 2005, is an informal coalition of societies representing professionals who work in or are concerned with interventional fluoroscopy. The group's long term goals are to improve occupational health and operator and staff safety in the interventional laboratory while maintaining quality patient care and optimal use of the laboratory. MSOHG has conducted a dialog with equipment manufacturers and has developed a list of specific objectives for research and development. The group has also represented the member societies in educating regulators, in educating interventionalists and in fostering and collaborating on research into occupational health issues affecting interventionalists. Not least of the group's accomplishments, as a result of their collaboration in MSOHG, the group's members have developed a mutual respect that can serve as a basis for joint efforts in the future among interventionalists of different medical specialties.